2013
DOI: 10.1186/1475-2891-12-31
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vitamin C as an adjunct to fluoxetine therapy in pediatric major depressive disorder: a randomized, double-blind, placebo-controlled pilot study

Abstract: BackgroundCurrent antidepressants used to treat pediatric patients have the disadvantage of limited efficacy and potentially serious side effects. The purpose of this study was to assess the efficacy of vitamin C as an adjuvant agent in the treatment of pediatric major depressive disorder in a six-month, double-blind, placebo-controlled pilot trial.MethodsThe study group (n=12) was given fluoxetine (10–20 mg/day) plus vitamin C (1000 mg/day) and control group (n=12) administered fluoxetine (10–20 mg/day) plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 66 publications
1
42
1
1
Order By: Relevance
“…Even in the present scenario ascorbic acid has been found to be effective in the mouse model of depression [34]. In a study done in the paediatric age group also the ascorbic acid treatment as an adjunct to fluoxetine has been found to be effective [35]. In our present study we evaluated the levels of ascorbic acid in major depression as compared to healthy controls and found the levels of ascorbic acid to be decreased significantly (p < 0.0001).…”
Section: Discussionmentioning
confidence: 89%
“…Even in the present scenario ascorbic acid has been found to be effective in the mouse model of depression [34]. In a study done in the paediatric age group also the ascorbic acid treatment as an adjunct to fluoxetine has been found to be effective [35]. In our present study we evaluated the levels of ascorbic acid in major depression as compared to healthy controls and found the levels of ascorbic acid to be decreased significantly (p < 0.0001).…”
Section: Discussionmentioning
confidence: 89%
“…Antidepressant properties have been described for other antioxidants as well (201,211,247,278,285). A randomized, double-blind, placebo-controlled pilot study in humans showed that the addition of vitamin C to antidepressant therapy significantly improved clinical outcomes (10). Addition of N-acetylcysteine to a tranylcypromine regimen also increased the response rate of patients with major depression who were resistant to conventional depression therapy (53).…”
Section: Indicators Of Oxidative Imbalancementioning
confidence: 99%
“…Patients treated for six months with fluoxetine and vitamin C showed a highly significant (p <0.0001) decrease in depressive symptoms compared to the fluoxetine plus placebo group as measured by the CDRS and CDI, but not CGI. These preliminary results suggest that vitamin C may be an effective add-on agent in the treatment of depression in paediatric patients (Amr et al, 2013).…”
Section: Vitamin C For the Treatment Of Paediatric Depressionmentioning
confidence: 91%
“…Only 4 studies were identified utilising this 'gold standard' research design. These include one study investigating the following nutrients; omega-3 PUFAs (Nemets et al, 2006), vitamin C (Amr et al, 2013), zinc (DiGirolamo et al, 2010, and iron (Lozoff et al, 2014). Unfortunately, these studies were compromised by small sample sizes and/or included participants with a lack of clearly defined major depression.…”
Section: Conclusion and Recommendations For Future Researchmentioning
confidence: 99%